2011
DOI: 10.1590/s0103-50532011000700025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dihydropyrimidin-2-one/thione library and cytotoxic activity against the human U138-MG and Rat C6 glioma cell lines

Abstract: Duas séries de 4-aril-3,4-diidropirimidin-2(1H)-(tio)onas incluindo monastrol (1a), foram sintetizadas por uma metodologia não agressiva ao meio ambiente baseada no uso combinado de ácido cítrico ou ácido oxálico na presença de TEOF (ortoformato de trietila). A atividade como inibidores da proliferação celular da quimioteca de compostos foi avaliada em duas linhagens de gliomas (U138-MG-humana e C6-rato). Os compostos derivados da tiouréia 1f e 1d mostraram atividade citotóxica maior do que a do monastrol. O c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Furthermore, the dioxide derivative (35) , like the dioxide derivative (24) (Table 2), and the saturated derivative (36) were bifunctional inductors (r H /B = 4.96 and r H /B = 2.05, respectively). In reference to the new derivatives of the tetrahydropyrimidine system we selected compounds where 2-thiocarbonyl and 4-phenyl groups were varied (derivatives (37–54) , Table 4) [27,28,36,37]. Unlike the parent tetrahydropyrimidinone (28) some of the 2-carbonyl derivatives, that is, (44) , (45) , (47) and (50) , were poor QR inductors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dioxide derivative (35) , like the dioxide derivative (24) (Table 2), and the saturated derivative (36) were bifunctional inductors (r H /B = 4.96 and r H /B = 2.05, respectively). In reference to the new derivatives of the tetrahydropyrimidine system we selected compounds where 2-thiocarbonyl and 4-phenyl groups were varied (derivatives (37–54) , Table 4) [27,28,36,37]. Unlike the parent tetrahydropyrimidinone (28) some of the 2-carbonyl derivatives, that is, (44) , (45) , (47) and (50) , were poor QR inductors.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, compounds that specifically inhibit Eg5 function have been identified, such as 3,4-dihydropyrimidin-2(1H)-one (or thione) (DHPMs) [ 22 - 24 ]. These molecules comprise a class of heterocyclic compounds obtained through Biginelli reaction that has monastrol as their prototype [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Eg5 inhibitors therefore not interfere with other microtubule-dependent processes [ 27 , 28 ], which are the main reason for the neurotoxicity of anti-microtubule agents [ 29 ]. It was shown that monastrol has antitumor activity against diverse cancer cell types such as renal, breast and glioma cell lines [ 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The great interest in pyrimidine and dihydropyrimidine (DHPM) derivatives lies in the fact that these classes of compounds has, in principle, pronounced biological activity [164,165]. Consequently, diverse methodologies have been developed to improve the synthesis of this attractive family of compounds [166].…”
Section: Pyrimidine-based Anticancer Heterocyclic Systemsmentioning
confidence: 99%